(untitled) (Journal of the College of Education for Women, 2019)
The Present study aims at answering the following questions:1-What is the level of the teaching style of biology teachers who teach (human and hishealth) 2-what is the level of healthy attitude to the teachers of biology who teach (human and hishealth).3- is there any relation between the teaching style of biology teachers who teach (human andhis health)and their student’s Ability Mind.4- is the any relation between the level of the healthy attitude to the teachers of biology whoteach (human and his health).The researcher made the following for the purpose of answering the question of the study:1-The card of observing the level of the teaching style (lecture style )to the teachers ofbiology who teach (human and his health).2- The measure of the healthy attitude.3- The measure of the Ability Mind.The researcher could find out the psychometric needed to be applied on the sample of thestudy as follows:1-Observation card: The researcher could find out:A-Credibility of the card: this is by displaying the on a group of exports and specialists inthe field education and psychology.b- The card stability: this is by re-observation between the researcher and himself throughtime and between the researcher and extra two observation .All the linkage coefficientwhere as following: 0.9 between the researcher and himself after two weeks, 0,87between the researcher and the observer, and finally o,88 between the two observers.2- The measure of healthy: the researcher could find out:a- The credibility of the measure: this is by displaying it on a group of experts andspecialists in the field of education, psychology and health.b- The stability of the measure: this is by re-testing .All the linkage coefficients were o,86 .3-The measure of healthy awareness: The researcher could find out:A-Measure Credibility: This is by displaying it on a group of experts and specialists in thefield of education, Psychology and health.B-Measure satiability: this is by –re testing .All the linking coefficients were 0.09.The sample of the study included 8 teachers and 95 students form daily intermediate schoolsfor boys in the central of najaf.the researcher could reach the following results:1-The first aim: there two levels of the style of the lecture for teachers of biology who teach(human and his health).2- The second aim: All teachers of biology enjoy a high level of healthy attitudes.3- The third aim: there is a close relationship between the teaching style level(lecture style) toteachers of biology who teach Ability Mind and the healthy awareness to their students.this relation is done by linking coefficients (spearman)which is 0,81.4- The forth aim: there is a close relationship between the healthy attitude to teachers ofbiology who teach (human and his healthy) and the healthy awareness to their students.this relation is done by the linkage coefficients) spearman) which is 0, 71.